2016
DOI: 10.1136/jech-2015-206800
|View full text |Cite
|
Sign up to set email alerts
|

Child academic achievement in association with pre-pregnancy obesity and gestational weight gain

Abstract: Background Recent data suggest that children of mothers who are obese before pregnancy, or who gain too much weight during pregnancy, may be at an increased risk of cognitive impairments. Methods Mother–infant dyads enrolled in a birth cohort study in Pittsburgh, Pennsylvania (1983–1986), were followed from early pregnancy to 14 years postpartum (n=574). Math, reading and spelling achievements were assessed at ages 6 and 10 years using the Wide Range Achievement Test-Revised, and at age 14 years using the We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
4
31
1
Order By: Relevance
“…16 Another recent meta-analysis aimed to evaluate the possible effect of exercise on the risk of preterm birth and found that exercise reduced the risk of preterm birth by 38% (RR = 0.62, 95% CI = [0.41-0.95]). Consistent with other studies, 13,[37][38][39]41,42,44 the current meta-analysis found no significant effect of exercise during pregnancy in overweight and obese pregnant women, on birthweight, preterm birth, small for gestational age, large for gestational age, or macrosomia at birth. The current meta-analysis examined the impact of exercise intervention alone for overweight and obese pregnant women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…16 Another recent meta-analysis aimed to evaluate the possible effect of exercise on the risk of preterm birth and found that exercise reduced the risk of preterm birth by 38% (RR = 0.62, 95% CI = [0.41-0.95]). Consistent with other studies, 13,[37][38][39]41,42,44 the current meta-analysis found no significant effect of exercise during pregnancy in overweight and obese pregnant women, on birthweight, preterm birth, small for gestational age, large for gestational age, or macrosomia at birth. The current meta-analysis examined the impact of exercise intervention alone for overweight and obese pregnant women.…”
Section: Discussionsupporting
confidence: 90%
“…2 Many studies have shown the adverse effects of maternal overweight and obesity during pregnancy. 12,13 Moreover, studies also found that overweight and obese women had low rates of breastfeeding initiation and duration with indirect disadvantage to their infant's growth and development. [5][6][7][8][9][10][11] In addition, children born to obese pregnant women have a higher risk of cardiovascular disease in later life than those born to normal-weight women.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gestational age was assessed from the last menstrual period, as ultrasound was not common at the time of the study, which could result in bias of our last maternal weight measurement timing due to measurement error, which would likely be nondifferential and bias results towards the null (Savitz et al, ). Finally, the cognitive tests reported are domain‐specific measures and are not direct measures of academic skills; however, our results for prepregnancy BMI are similar to another report with academic outcomes in childhood (Pugh et al, ). Strengths include our ability to examine two cognitive outcomes, reflecting different cognitive domains, with a relatively large sample size and with adjustment for a range of confounders, including maternal education and, in a subset, maternal IQ.…”
Section: Discussionsupporting
confidence: 86%
“…Two studies reported results consistent with ours for prepregnancy body size, but in contrast to our report, observed associations between GWG and child outcomes. In a Pittsburgh cohort, maternal prepregnancy BMI values above 22 kg/m 2 and high GWG were each associated with lower reading, math, and spelling scores ages 6, 10, and 14 years (Pugh et al, ). In a United Kingdom cohort, prepregnancy weight was inversely associated with IQ at age 8 years, and GWG from early to mid‐pregnancy (0–28 weeks) was positively associated with child IQ (Gage et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation